Fetal ovarian cyst. a case report - Monzón Castillo, Eli Pedro (2020)
Ovarian cysts are the most common abdominal tumors in female newborns. Among the acute and long-term complications, the most frequent is the adnexal torsion, which is difficult to recognize in the neonatal stage. Prenatal diagnosis is essential for the timely management of patients and ultrasound monitoring of adnexal cysts. There are different therapeutic alternatives where minimally invasive and conservative surgery plays an important role.